CHEMILUMINESCENCE INTENSITY, ANTIOXIDANT SYSTEM STATE AND OXIDATIVE MODIFICATION OF PROTEINS IN BLOOD IN OVARIAN CANCER PATIENTS WITH A LOCAL RECURRENT TUMOR - I. A. Goroshinskaya; G. A. Nerodo; E. I. Surikova; P. S. Surikova; V. V. Vnukov; E. V. Shalashnaja; I. V. Neskubina; L. A. Nemashkalova; N. A. Maximova; M. M. Sergeeva (Сибирский онкологический журнал)
The state of antioxidant system (the activity of catalase and ceruloplasmine), the intensity of chemiluminescence, and oxidative modification of proteins were studied in blood plasma of 61 patients with ovarian cancer (cystadenocarcinoma) III–IV stage in state of remission and ones with a local recurrent tumor. The dynamics of these indices was analyzed in dependence of recurrent tumor vascularization. The statistically significant changes of the activity of some links of antioxidant system were found, as well as chemiluminescence intensity increase in blood plasma. The level of oxidative modificated protein molecules was raised, the most expressed for products of the main character (530 nm). The dynamics of level of carbonyl derivatives of the neutral and main character (370 and 530 nm) was opposite directed during intensification of recurrent tumour vascularization and increase in speed of blood-groove in a recurrent tumor